Case Report: A novel likely pathogenetic variant of the MEN1 gene in multiple endocrine neoplasia type 1 - Sun, Mengli; Chang, Xinxia; Huang, Xianen; Chen, Liangmiao; Peng, Mengmeng; Zhong, Xiqiang (Frontiers in Endocrinology, 2025)
BackgroundMultiple endocrine neoplasia type 1 (MEN1) is a rare disease caused by mutations in the oncosuppressor gene MEN1 and characterized by co-occurrence of tumors of the parathyroid gland, pancreas, and pituitary gland. The clinical manifestations of MEN1 are varied, and misdiagnosis is common. The life expectancy of patients with untreated MEN1 is short. Here, we report a case of a 50-year-old patient with recurrent urinary calculi for more than 10 years who had a pancreatic neuroendocrine tumor and parathyroid adenoma. The patient received a definitive diagnosis of MEN1. We analyze his clinical characteristics and describe our approach to management.Case PresentationLaboratory tests showed high parathyroid hormone (PTH), high blood calcium, and low blood phosphorus levels and increased excretion of urinary calcium. Immunohistochemical analysis showed loss of menin expression in pancreatic tumor tissues. Testing of the MEN1 gene revealed a variant in exon 9 (c.1257_1268del, p.lle420_Trp423del).ConclusionThe patient’s clinical characteristics combined with the testing of the MEN1 gene, it implied the variant was a novel likely pathogenetic variant. For patients with recurrent urinary stones, we recommend measuring blood calcium and PTH, and if there are abnormalities, screening other endocrine glands to exclude the possibility of MEN1.